Serum parameters of inflammatory markers as prognostic biomarkers with maternal-neonatal outcome in patients with GDM - Xiu, Xiaoyan; Lin, Yingying; Chen, Zhiwei; Lin, Lin; Zu, Yizheng; Yan, Jianying (Frontiers in Medicine, 2024)
Objective Gestational diabetes mellitus (GDM) is one of the most common complications of pregnancy, which is increasing annually. GDM can cause serious harm to both the mother and the offspring. However, the clinical indicators that predict pregnancy outcomes with GDM remain limited. Methods This study included 3,229 pregnancies. Inflammatory markers were defective in the mother’s peripheral blood. Also, the Chi-square test, logistic regression analyses and Spearman rank correlation coefficient were performed to evaluate inflammatory markers with pregnancy outcomes. The association between inflammatory markers and pregnancy outcomes was analyzed. The optimal cut-off values of inflammatory markers were calculated. Results Finally, 3,229 women were included. 1852 (57.36%) participants suffered good pregnancy outcomes. This study revealed that the maternal age, the baseline BMI (kg/m2), the times of parity, and the level of lymphocyte, SII and SIRI significantly increased in poor pregnancy outcomes groups. Additionally, inflammatory markers, such as white blood cells (WBC), neutrophils, monocytes, platelet counts, lymphocytes, systemic immune-inflammation index (SII) and systemic inflammation response index (SIRI) were related to pregnancy outcomes. Furthermore, the results revealed that the SII level had the highest odd rates (OR) [OR = 6.957; 95% CI (5.715–8.468)], followed by SIRI level [OR = 2.948; 95% CI (2.382–3.649)], the WBC counts [OR = 1.930; 95% CI (0.901–2.960)], the lymphocyte counts [OR = 1.668; 95% CI (1.412–1.970)], and baseline BMI [OR = 1.050; 95% (1.021–1.080)]. Conclusion This study presented that the baseline SII and SIRI levels can be valuable biochemical markers to predict the pregnancy outcome with GDM with non-invasive procedures. They can help identify high-risk pregnant women with GDM early, provide a personalized intervention in time, and enhance perinatal surveillance.